DEVELOPMENT PROSPECTS OF THE OIL PRODUCTION INDUSTRY IN THE REPUBLIC OF UZBEKISTAN AND FOREIGN COUNTRIES - Bozorov, Sardor; Kurbanov, Nematilla (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
High-performance mills equipped with modern equipment in the Republic of Uzbekistan. Technological processes in mills and flour mills in foreign countries do not fundamentally differ from technological processes used in factories in the Republic of Uzbekistan. Attention is paid to the quality of flour, which is compared with the constructions of machines used only in technological processes.